Penghambatan aktivitas peneluran kumbang kacang hijau Callosobruchus Chinensis L. (Coleoptera: Bruchidae) oleh extrak sepuluh spesies tumbuhan - Dadang Dadang; U. Undayasari (Perhimpunan Entomologi Indonesia, 2005)
Oviposition Deterrence of Bean Weevil, Callosobruchus chinensis L.(Coleoptera: Bruchidae) Treated with Ten Plant Extracts. Pest and Diseases attack agricultural products not only in the field but also in storehouse. Their attack causes decreasing both quantity and quality of stored materials. One of important stored product insect pests is Callosobruchus chinensis L. (Coleoptera: Bruchidae). Till now the effective strategy to control this insect pest is chemical control by using synthetic insecticides. The improper use synthetic insecticides causes some undesirable effects, so alternative strategist should be searched to controls insect pests in storehouse. One of the alternatives is by using plant materials as insect pests control agent. The aim of this study was to find out the oviposition deterrence of C. chinensis treated with ten plant which were extracted with methanol, hexane and ether. Oviposition deterrence was evaluated by choice and no-choice methods at 1,3 and 5% of extract concentration. Extract of Acorus calamus (methanol), A.calamus (hexane), A. calamus (ether), Illicium verum (ether), Pogostemon calbin (hexane), P. cablin (ether), Vetiveria zizanioides (hexane), and V. zizanioides (ether) were able to deter ovipostion activity of C. chinensis by more than 90% of deterrence. Further study should be conducted to isolate and identify the active compound and to make botanical insecticide formulation for practical use as a commercial product.